Resolving a clinical tuberculosis outbreak using palaeogenomic genome reconstruction methodologies - Llinos Harris (Tuberculosis, 2019)
This study describes the analysis of DNA from heat-killed (boilate) isolates of Mycobacterium tuberculosis from two UK outbreaks where DNA was of sub-optimal quality for the standard methodologies routinely used in microbial genomics. An Illumina library construction method developed for sequencing ancient DNA was successfully used to obtain whole genome sequences, allowing analysis of the outbreak by gene-by-gene MLST, SNP mapping and phylogenetic analysis. All cases were spoligotyped to the same Haarlem H1 sub-lineage. This is the first described application of ancient DNA library construction protocols to allow whole genome sequencing of a clinical tuberculosis outbreak. Using this method it is possible to obtain epidemiologically meaningful data even when DNA is of insufficient quality for standard methods.